Diabetic Foot Syndrome From Entity to Therapy - Hochlenert, Dirk (Springer International Publishing, 2018)
This book provides a clear and integrated guide to the diagnostic pathways and therapeutic options available for the treatment of diabetic foot syndrome. The link between the location of the lesion and its potential causes are discussed in relation to its diagnosis, biomechanics, treatment and prognosis. Chapters covering interdigital lesions, the lateral side of the foot, torsion of the hallux, and the charcot foot are included. Diabetic Foot Syndrome: From Entity to Therapy aims to facilitate interdisciplinary understanding and is relevant to endocrinologists, as well as vascular and orthopedic surgeons.